Modeled spatial-temporal distribution of productivity, chlorophyll, iron and nitrate on the northern Gulf of Alaska shelf relative to field observations. (July 2019) - Coyle, K.O.; Hermann, A.J.; Hopcroft, R.R.
Abstract: The northern Gulf of Alaska (GOA) shelf is dynamic spatially and temporally. With two major current systems and numerous eddies and meanders, interpretation of field data from ship-based observations at specific times and locations is complicated. We used the Regional Ocean Modeling System (ROMS) with an embedded nutrient-phytoplankton-zooplankton (GOANPZ) model to aid in understanding spatial-temporal patterns of productivity, chlorophyll concentration and biomass over the GOA shelf between 132 o W and 160 o W from 2000 to 2013. Carbon chlorophyll ratios in the model were varied in response to light to alter production-irradiance curves by season to conform to field measurements. Simulations reveal regions of high productivity in March–May on the southeast Alaskan Shelf, and the western inner shelf between Prince William Sound (PWS) and the Shumagin Islands, but with lower productivity on the outer shelf between PWS and western Kodiak. The model produced regions of elevated productivity on the outer shelf of the western GOA during summer and fall. This pattern is driven by circulation affecting the distribution of iron on the western shelf. Simulated productivity on the shelf between 2000 and 2006 was elevated relative to 2007–2013, apparently due to changes in the simulated iron concentration. Correlations indicate that simulated production on the western GOA shelf during March–May can explain up to 65% of the variance in the mean biomass of large copepods from net tows during spring. Simulations suggest that detailed temporal-spatial data on iron concentration and the processes affecting iron are crucial to understanding interannual spatial-temporal differences in magnitudes of production and biomass at lower trophic levels on the GOA shelf.